The Implementation of Diversion in Juvenile Criminal Justice System in North Sumatra: Challenges and Legal Effectiveness - Ica Karina; Maidin Gultom (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
The implementation of diversion in the juvenile criminal justice system remains a crucial issue because children in conflict with the law require legal protection, rehabilitation, and social reintegration rather than punitive treatment. Although Law Number 11 of 2012 concerning the Juvenile Criminal Justice System mandates diversion at the stages of investigation, prosecution, and court examination, its practical implementation in North Sumatra still faces various institutional, procedural, and socio-cultural challenges. This research addresses three main questions: how diversion is implemented in juvenile criminal cases in North Sumatra, what obstacles affect its implementation, and how effective diversion is as a legal mechanism for achieving restorative justice. This study uses a socio-legal research design with a descriptive-analytical approach. Data were collected through library research, document study, observation, and interviews with legal actors and related stakeholders involved in the diversion process. The findings show that diversion has been formally recognized and applied, but its effectiveness remains partial. Diversion is more successful when conducted at the earliest stage of the criminal process, when victims are willing to participate, families provide support, and law enforcement officials actively facilitate restorative dialogue. However, several obstacles remain, including different understandings among law enforcement officers, weak institutional coordination, limited trained facilitators, inadequate facilities, low victim participation, and punitive legal culture. This article contributes academically by offering a contextual analysis of diversion implementation in North Sumatra and demonstrating that the legal effectiveness of diversion depends not only on statutory regulation, but also on institutional readiness, community participation, victim involvement, family support, and continuous monitoring of diversion agreements.